攻讀跨國雙聯博士學制之國際移動體驗與 意涵：以比利時臺灣雙聯博士學位學生為例 Multidimensional Meanings of Studying Abroad: International Mobility Experiences of Taiwanese Joint Dual Doctoral Program Students in Belgium - Hsien-Ming Lin 林顯明; Yu-Hsien Sung 宋宥賢; Li-Chun Wang 王俐淳 (National Taiwan Normal University, 2020)
推動雙聯博士學制是近年來臺灣高等教育機構推動國際化及提升博士班招生吸引力的重要策略。然而，關於臺灣學生赴海外攻讀雙聯博士學位之相關研究則尚未可見。對此，本研究藉由質性研究途徑之自我民族誌和半結構式訪談法，探究學生赴海外攻讀雙聯博士學位之國際移動體驗與意涵，共七位參與臺灣和比利時雙聯博士學制計畫（跨機構聯合雙學位）的學生及教授參與本研究。本研究發現，這些學生原有赴海外攻讀博士學位的規劃，而時間、經費等成本效益計算，以及創造在學術環境中的差異性與獨特性等考量，皆是促使其參與雙聯博士學制之重要因素。而在赴海外學習的過程中，跨文化溝通、兩國培育機制、東西方文化與教授指導方式之差異等，都對學生產生學習和適應上的挑戰，然其在過程中亦發展出調適策略，並逐漸找到自身價值、學術定位與認同感。但由於相關規定對海外修業時間的限制，使得這些學生在參與當地社會及拓展當地人際關係網絡產生侷限；此外，社會對此學制的理解有限與誤解，亦可能負向影響雙聯博士學位畢業生在學術就業職場上的移動能力，以及未來學生參與此學制之意願。就此，本研究亦提出相關實務與研究建議，以促進未來雙聯博士學制之推動。 Promoting dual doctoral degree programs is a critical strategy adopted to not only internationalize Taiwan's higher education system but also improve the low enrollment rates in doctoral programs in the country. However, limited research attention has been paid to the experiences of Taiwanese students enrolled in dual degree programs. Therefore, the present study adopted a qualitative approach to explore the experiences of Taiwanese students enrolled in a Taiwanese-Belgian joint dual doctoral program. A total of seven Taiwanese students and Belgian scholars participated in this study. The findings indicated that all student informants intended to study abroad before deciding to participate in the joint dual doctoral program; however, due to time and money restrictions, they participated in the joint dual doctoral programs established by their home universities in Taiwan. This study highlighted that students were motivated to participate in international, cooperative doctoral programs because obtaining dual learning experiences at both domestic and overseas universities differentiated them from purely domestic doctoral students. In this manner, the experience of studying abroad enhances their unique value in the academic market. While studying abroad, intercultural communication, in addition to differences in doctoral training schemes and supervision styles, were vital challenges that affected student informants' learning experiences and adaptation to life. During this process, the students constructed their adaptation and negotiation strategies to address those challenges. These strategies made them (re)define and (re)confirm their academic positions and identities. However, the limited period for studying abroad reduced students' motivation to participate and engage in local activities and establish social networks with local residents and friends in the host society. Moreover, the public and academic colleagues' limited understanding of the joint dual doctoral program may not only negatively affect students' academic mobility in terms of obtaining positions in the academic market but also influence prospective students' willingness to participate in such programs. Moreover, this study provides constructive suggestions for the development of joint dual doctoral programs on the basis of students' own practical experiences. Finally, the study's limitations and suggestions for future research are discussed.